Differential Effects of Orientation and Spatial-Frequency Spectra on Visual Unpleasantness - Ogawa, Narumi; Motoyoshi, Isamu (Frontiers in Psychology, 2020)
Increasing psychophysical evidence suggests that specific image features - or statistics - can appear unpleasant or induce visual discomfort in humans. Such unpleasantness tends to be particularly profound if the image's amplitude spectrum deviates from the regular 1/f spatial-frequency falloff expected in natural scenes. Here, we show that profound unpleasant impressions also result if the orientation spectrum of the image becomes flatter. Using bandpass noise with variable orientation and spatial-frequency bandwidths, we found that unpleasantness ratings decreased with spatial- frequency bandwidth but increased with orientation bandwidth. Similarly, a subsequent experiment revealed that sinusoidal modulations in the amplitude spectrum of 1/f noise along the spatial frequency increased unpleasantness, but modulations along the orientation decreased it. Given that natural scenes tend to have a linear slope along the spatial frequency but an uneven spectrum along the orientation dimension, our opposing results in the spatial-frequency and orientation domains commonly support the idea that images deviating from the spectral regularity of natural scenes can give rise to unpleasant impressions.